2023
DOI: 10.1021/acs.biomac.2c01232
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-Derived Polymers as Potential Biomaterials: Synthesis Strategies, Properties, and Applications

Abstract: Peptide-based polymers are evolving as promising materials for various biomedical applications. Among peptidebased polymers, polytyrosine (PTyr)-based and L-tyrosine (Tyr)derived polymers are unique, due to their excellent biocompatibility, degradability, and functional as well as engineering properties. To date, different polymerization techniques (ringopening polymerization, enzymatic polymerization, condensation polymerization, solution-interfacial polymerization, and electropolymerization) have been used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 187 publications
0
10
0
Order By: Relevance
“…In this study, we showed that some tyrosine residues underwent iodination in the presence of TPO, while in the absence of TPO virtually no iodinated tyrosine was produced. Although tyrosine has a phenolic hydroxyl structure and is prone to oxidation in the presence of oxides, a higher concentration of I 2 was found to have stronger oxidative properties in aqueous solution 21 . In system IV, tyrosine was found to be involved in two types of competing reactions: iodination and oxidation.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we showed that some tyrosine residues underwent iodination in the presence of TPO, while in the absence of TPO virtually no iodinated tyrosine was produced. Although tyrosine has a phenolic hydroxyl structure and is prone to oxidation in the presence of oxides, a higher concentration of I 2 was found to have stronger oxidative properties in aqueous solution 21 . In system IV, tyrosine was found to be involved in two types of competing reactions: iodination and oxidation.…”
Section: Discussionmentioning
confidence: 96%
“…It is worth mentioning that we conducted a series of experiments on synthesizing CLCP-1 with different feeding ratios of p-phenylenediamine: M-CHO from 2:1 to 12:1.We found that the crystallinity was highest at the feeding ratio of 1:6, which was chosen as the optimized synthesis condition (Figure S20). The bond-forming reaction of CLCP-1 and -2 was confirmed by Fourier transform infrared spectroscopy (FT-IR) and solid-state 13 S2). The reflection condition can be determined as hkl: h + k = 2n; h0l: h, l = 2n from the 2D slices that were cut from the 3D reciprocal lattice, which suggests two possible space groups: Cc (no.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Recently, we have reviewed various synthesis strategies and applications of PTyr-based and L-Tyrderived polymers. 35 Importantly, Tyr transfers an electron and a proton upon electrooxidation. A fully oxidized PTyr of high molecular weight can generate plenty of electrons to amplify the electrochemical signal, and PTyr shows ideal properties over conventional CPs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, (PTyr) and polyhistidine are soluble and have already been investigated in sensing applications. , Importantly, l -tyrosine (Tyr) is an aromatic amino acid, and the conjugated structure of PTyr with low electron tunneling barriers contributes to its excellent conducting properties. Recently, we have reviewed various synthesis strategies and applications of PTyr-based and l -Tyr-derived polymers . Importantly, Tyr transfers an electron and a proton upon electrooxidation.…”
Section: Introductionmentioning
confidence: 99%